1994
DOI: 10.1063/1.112783
|View full text |Cite
|
Sign up to set email alerts
|

Effect of interfaces on the electrical behavior of (Pb0.72La0.28)TiO3 thin films

Abstract: Paraelectric (Pb0.72La0.28)TiO3 or PLT(28) thin films were deposited on platinum coated Si substrates by the sol-gel technique. Two distinct groups of top metals, namely MT (Ni, Cr, and Ti, i.e., transition metals) and MN (Pt, Au, and Ag, i.e., noble metals) formed Ohmic and Schottky contacts, respectively. A Schottky barrier height of 1.83 eV at the Pt-PLT interface was determined. The conventional Schottky emission and Fowler–Nordheim tunneling equations were modified to account for the voltage dependence of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

1995
1995
2013
2013

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 4 publications
0
8
0
Order By: Relevance
“…As shown earlier, the individual impedances of three or more capacitors in series ͑as in the Zr-O/IL/Si stack͒ are influenced by their nanostructure, nanochemistry, thickness, and includes contributions from space-charge regions near grain boundaries, defects, and electrodes. 23,86,87 Due to the uncertainties in the magnitude of t, k, and ͑or C p s and R p s) of the three distinct regions, coupled with the uncertainties in the magnitude of the relaxation components in the Zr-O layer, it is difficult to quantify the frequency dispersive behavior ͑Table II͒. This also explains why a simple bilayer ͑capacitance only͒ model fails in the case of Zr-O/IL/Si stacks that had SiO as the initial growth surface, as well as in stacks with t ZrϪO Ͻ5 nm.…”
Section: Top Zr-o Layermentioning
confidence: 98%
“…As shown earlier, the individual impedances of three or more capacitors in series ͑as in the Zr-O/IL/Si stack͒ are influenced by their nanostructure, nanochemistry, thickness, and includes contributions from space-charge regions near grain boundaries, defects, and electrodes. 23,86,87 Due to the uncertainties in the magnitude of t, k, and ͑or C p s and R p s) of the three distinct regions, coupled with the uncertainties in the magnitude of the relaxation components in the Zr-O layer, it is difficult to quantify the frequency dispersive behavior ͑Table II͒. This also explains why a simple bilayer ͑capacitance only͒ model fails in the case of Zr-O/IL/Si stacks that had SiO as the initial growth surface, as well as in stacks with t ZrϪO Ͻ5 nm.…”
Section: Top Zr-o Layermentioning
confidence: 98%
“…It is known that electrical contacts between FE and transition metals are different from those made out of noble metal electrodes. 10 It was suggested that the transition metals easily form oxides and result in the n-type semiconducting interface layer. 11 Then, the Cr/BTO interface will accompany positive donor ions, thereby reducing the asymmetric switching.…”
mentioning
confidence: 99%
“…Other workers reported that similar rectifying behaviors could be induced when asymmetric top and bottom interfaces were formed in capacitor structures. 12,14,15 They argued that different kinds of top and bottom electrode materials should induce asymmetric top and bottom interfaces. However, in our capacitor structure, the only difference between the top and the bottom electrodes comes from different thermal processes experienced by the electrodes.…”
Section: A Asymmetries Induced By Thermal Processesmentioning
confidence: 99%
“…9͑b͒. 14,20,21 The capacitances at the top and the bottom interfaces were denoted by C i t and C i b , respectively. In this analysis, the total capacitance can be written by…”
Section: B Electrical Characterization Of the Interfacesmentioning
confidence: 99%